The The Students’ Ability to Identifying Dependent and independent clauses in Sentences - Sariakin Sariakin; Anwar Anwar (Kodepena Indonesia, 2020)
Abstract The purposes of this research are (1) to find out how the students’ ability of English department of training and teacher educational faculty of Serambi Mekkah University in identifying dependent and independent clauses in sentences is and (2) to find out the factors that influence the students ‘ ability of English department of training and teacher educational faculty of Serambi Mekkah University confuse in identifying dependent and independent clauses in sentences. The method used is descriptive analysis. Data needed are gotten through test. The data gotten are analyzed by analyzing and discussing. The result of the study shows that the students’ ability in identifying dependent and independent clauses in sentences is in sufficient category because the students’ average score is 57.43. Thus the students’ ability in identifying dependent and independent clauses in sentences is not satisfying. Next, many students are still confused to construct adjective clause, noun clause, and adverbial clause because there are so many conjunctions that are different in their use in constructing the dependent clauses. Therefore, the students still get difficulties to indentify dependent and independent clauses in sentences.